ANALISIS PERBANDINGAN PRODUKTIVITAS KEGIATAN PETAMBAK UDANG VANAMEI (Litopenaeus vannamei) SISTEM TRADISIONAL PADA DUA DESA DI KAWASAN EKOSISTEM ESENSIAL MANGROVE UJUNGPANGKAH - Maulidda Alfajar Syaifullah; Farikhah Farikhah; Andi Rahmad Rahim (Jurnal Perikanan Pantura (JPP), 2022)
The Ujungpangkah Mangrove Essential Ecosystem Area is a coastal village area that has high biodiversity and has a large role status for the Ujungpangkah community whose livelihoods are in the fishery sector including shrimp farming. The purpose of this study was to analyze the productivity of the traditional vannamei shrimp pond system in Ujungpangkah District. There are several variables that become the productivity of vannamei shrimp ponds including aspects of farmers, aspects of land ownership, technical aspects of cultivation, input aspects, cost aspects and output aspects. This research method is descriptive quantitative which includes analysis of T test and qualitative which includes correlation which includes density of fry, seed, price of fry and price of feed associated with yields and income. There were 20 respondents in this study in each village. The results of the analysis of the T-test of Pond Productivity found that the price of fry and feed prices had a significant difference (P<0.05) in increasing the productivity of ponds in two villages, Ujungpangkah sub-district. Furthermore, the results of the correlation analysis from all aspects including (density of fry, seeds, feed prices, prices of fry) have a positive relationship to harvest yields and income in Pangkahkulon and Pangkahwetan villages, Ujungpangkah sub-districts. With variables that have a weak and sufficient relationship between each observation parameter. It is known that the analysis of vannamei shrimp farming business B/C ratio in the two villages of Ujungpangkah District reached the break-even point of 1 so that the business in aquaculture was still feasible to continue. Furthermore, the Break event point (BEP) of Pangkahkulon reached the break even point with a BEP value of 484.89 kg, while Pangkahwetan reached a break even point with a BEP value of 310.9 kg, which means that the two villages did not experience losses.